Mucosal Immunity and acute viral gastroenteritis - Rose, Markus A (Human vaccines & immunotherapeutics, 2014)
Acute gastroenteritis is a major killer of the very young worldwide. Rotavirus is the most common intestinal virus, causing acute gastroenteritis and extra-intestinal complications especially in young and chronically ill subjects. As early as 1991, the WHO recommended as high priority the development of a vaccine against rotavirus, the major pathogen causing enteric infections. Since the introduction of rotavirus vaccines for infant immunization programmes in different parts of the world in 2006, vaccination against rotavirus has resulted in substantial declines in severe gastroenteritis. The oral rotavirus vaccines RotaTeq(®) and Rotarix(®) are excellent examples for their unique features and principles of mucosal immunization. We elaborate on rotavirus immunity and the success of rotavirus vaccination and aspects also beyond infants' acute gastroenteritis.